2022
DOI: 10.20944/preprints202206.0088.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Energy Model for an Optimal Design of a Hybrid Refrigerated Van

Abstract: The path towards decarbonization requires a progressive adaptation of all refrigeration systems, but only stationary ones have been intensely studied to improve their environmental performance. However, refrigerated transport is a vital piece of the cold chain, and it must be considered in the green transition. In this paper, we propose a model for a hybrid refrigerated van that includes photovoltaic panels and electric batteries to decrease total greenhouse gas emissions from the engine. Thermal, electrical, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Angelo et al used water as the PCM, and put 15.6 kg of tap water on the bare tube evaporator. The results showed that the introduction of PCM reduced the fluctuation of product temperature during the operation of the refrigerator and the temperature difference between the top and the bottom of the refrigerator, and prolonged the OFF time of the compressor [4]. Khan et al experimentally studied the use of PCMs behind the five sides of the evaporator.…”
Section: Introductionmentioning
confidence: 99%
“…Angelo et al used water as the PCM, and put 15.6 kg of tap water on the bare tube evaporator. The results showed that the introduction of PCM reduced the fluctuation of product temperature during the operation of the refrigerator and the temperature difference between the top and the bottom of the refrigerator, and prolonged the OFF time of the compressor [4]. Khan et al experimentally studied the use of PCMs behind the five sides of the evaporator.…”
Section: Introductionmentioning
confidence: 99%